(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The vital importance of the role of grammar instruction in foreign language learning is that some teachers and readers think grammar instruction is not necessary for learning language. However, other researchers suppose its role is very significantable among the majority of studies. Students would not learn speaking, reading, listening, and writing skills if they did not know anything about how structure grammar rules of word and sentences.